Exploring the influence of indigenous knowledge systems on entrepreneurial innovation: An emerging market perspectives in the context of South African women entrepreneurs - Chipp, Kerry (University of Pretoria, 2025)
Mini Dissertation (MBA)--University of Pretoria, 2024.